EZH2 Inhibitors Suppress Colorectal Cancer by Regulating Macrophage Polarization in the Tumor Microenvironment - Li, Chen; Song, Jiagui; Guo, Zhengyang; Gong, Yueqing; Zhang, Tengrui; Huang, Jiaqi; Cheng, Rui; Yu, Xiaotong; Li, Yanfang; Chen, Li; Ma, Xiaojuan; Sun, Yan; et al. (Frontiers in Immunology, 2022)
EZH2 inhibitors (EZH2i), a class of small-molecule inhibitors target to EZH2 to exert antitumor function, has just been approved by the US Food and Drug Administration (FDA) in treatment of adults and adolescents with locally advanced or metastatic epithelioid sarcoma. The application of EZH2i in several solid tumors is still in different stages of clinical trials and need to give further explicit indication. As a key epigenetic regulator, besides its role in controlling the proliferation of tumor cells, EZH2 has been implicated in the regulation of various immune cells including macrophages as well. But there are still controversial research results at present. Colorectal cancer (CRC), one of EZH2 highly expressed tumor, is a common malignant tumor, which ranks the third high incidence and second leading cause of cancer-related deaths worldwide. Studies have shown that the numbers of M2 type tumor-associated macrophages (TAMs) is highly associated with the progression and metastasis of CRC. In current study, we aim to investigate how EZH2 modulates the polarization of macrophages in tumor microenvironment (TME) of CRC, and compare the role of two different EZH2 inhibitors, EPZ6438 and GSK126. We applied 3D culture method to demonstrate EZH2i indeed suppress the proliferation of CRC cells in vitro. In vivo, we found that the percentage of CD206+ macrophages of TME was decreased under the treatment of EPZ6438, but it increased upon GSK126 treatment. Besides, in co-culture system of macrophages and CRC cells, EPZ6438 led to significant elevation of M1 markers and reduction of M2 markers. Furthermore, mechanistic studies validated by ChIP-qPCR demonstrated that EZH2i inhibit EZH2-mediated H3K27me3 levels on the promoters of STAT3, an essential transcription factor for M1 macrophages polarization. Therefore, our data suggested that EZH2i not only suppress CRC cells proliferation directly, but also regulate macrophages by skewing M2 into effector M1 macrophages to exert tumor suppressive effect. Moreover, our study provided new insight for better understanding the role of two kinds of EZH2i: EPZ6438 and GSK126, which may pave the promising way in treating CRC both targeting the cancer cells and immune cells by this epigenetic approach in the future.